(untitled) (Revista Médica de Trujillo, 2025)
Objetive: To determine the relationship between medical prescription and drug use in patients of the Regional Teaching Hospital of Trujillo. Methods: Quantitative, non-experimental, descriptive-correlational study. A total of 302 prescriptions of SIS patients attended in the hospitalization pharmacy were evaluated by means of structured questionnaires and data collection, contrasted with the WHO indicators of rational drug use. Results: The level of medical prescription was good in 41.39%, fair in 34.77% and poor in 23.84%. Medication use was adequate in 57.62% and inadequate in 42.38%. Conclusion: Medical prescription is significantly related to the use of medications in hospitalized patients affiliated to the Comprehensive Health Insurance in the study hospital.